MANAJEMEN PEMBINAAN GURU DALAM PERSPEKTIF ISLAM: TELA’AH AL QUR’AN SURAH AN NAHL AYAT 125 - Saekan, Mukhamad (CV. Lafadz Jaya, 2024)
The Qur'an was revealed to humans as guidance and guidelines in life. Teachers, who are Muslims, must carry out their duties based on the message of the holy book of the Qur'an. The ideal teacher profile in carrying out duties and responsibilities cannot appear suddenly but needs to be done with a process carried out continuously and systematically. One of the efforts to foster teachers is based on the values in verse 125 of Surah A nahl. This type of research is a literary category (literature review), a process of actions related to collecting library data, reading and recording, and analyzing materials and research results. This research examines verse 125 of Surah An Nahl, which is associated with the management of coaching teachers in carrying out their duties and authority as educators and teachers. The data collection technique used is a literature study done by reading books or magazines with other data sources in the library relevant to the research theme. Data analysis is carried out with sociological text analysis techniques, namely examining the relevance of the text (verse). Verse 125 of Surah An Nahl is associated with social attitudes and behavior for teachers in carrying out their duties and responsibilities as educators and teachers so that an ideal teacher profile can be produced according to Islamic views. There are 3 (three) findings of this study. First, teacher coaching management in perspective in verse 125 of Surah An nahl is a coaching pattern that prioritizes a humanistic, contextual, and procedural approach so that it can give birth to an ideal teacher profile in the current era. Second, implementing three concepts in verse 125 of Surah An Nahl, namely bil al hikmah (by wisdom), mauidhah hasanah (good advice), and jidal (debate), in teacher coaching management is not understood in parts and stages but is understood synergistically, proportionally, and realistically. Third, three kinds of concepts in verse 125 of Surah An Nahl, in addition to being used as an approach in coaching management, must also be used as a product/result of teacher coaching management.